Assessing Human Needs Theory: An Approach to Conflict Resolution - A. Azam; S. Rehman (The Nucleus, 2025)
John Burton’s Human Needs Theory has been a cornerstone for conflict resolution, emphasizing that there are vital needs that all human beings have in common and if desecrated, may result in conflict. Indeed, unfulfilled needs are the root cause of a conflict hence; if human needs are denied or obstructed then conflict is inevitable. John Burton’s Human Needs Theory may not present a comprehensive conflict resolution mechanism rather it focuses to provide basic understanding and identification of factors that are likely to cause conflict. Burton’s work may be regarded as baseline study of theory of conflict formation aimed at identifying causation of factors and levels contributing to conflict rather resolution specifically. However, in his subsequent writings Burton attempted to bridge the gap between Humans needs theory and conflict resolution by describing framework to resolve a conflict. Nonetheless, besides offering so much, assertion of Burton’s theory may be further argued and analyzed in the current milieu of international affairs. This paper seeks to understand the causes of conflict at the societal or state level through the prism of human needs theory.